Made of steel eaudiobook - Smoak, Ivy (Made of Steel, 2019)
The witness protection program has given me the fresh start I've always dreamed of. A new home. A new name. A new life. For the first time in ten years it feels like I can breathe again. But the cost of freedom is more than I bargained for. I put my foster father behind bars. It doesn't matter that he deserved it. What matters is that he's powerful, manipulative, and now he wants me dead. I can feel someone watching me. I know my time is running out. And the only other person who cares if I live or die is a masked stranger. So I'm putting my life in the vigilante's hands. And maybe a piece of my heart along with it. Even though I'm worried that he's just as dangerous as the man I sent to prison.